Service Supply Chain Performance In Malaysian National Car Service Centres: The Role Of Service Supply Chain Management Practices, Service Innovation Capability And Value Co-Creation - Janteng, Jaludin (2020)
Service supply chain is a business strategy from the perspective of supply chain management. It enables organisations to achieve competitive advantage and profitability. However, studies on service supply chain performance measurement are limited in literature. Therefore, the aim of this study is to investigate the relationship of service supply chain management practices towards service supply chain performance through the mediating role of service innovation capability. To develop a comprehensive view of service supply chain, value co-creation is included in the research model as moderating variable in enhancing service supply chain performance. Resource-based and Relational theory were used to explain the relationship among variables in the proposed model